2011
DOI: 10.1111/j.1740-8709.2011.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization (WHO) infant and young child feeding indicators: associations with growth measures in 14 low‐income countries

Abstract: Eight World Health Organization (WHO) feeding indicators (FIs) and Demographic and Health Survey data for children <24 months were used to assess the relationship of child feeding with stunting and underweight in 14 poor countries. Also assessed were the correlations of FI with country gross national income (GNI). Prevalence of underweight and stunting increased with age and Ն50% of 12-23-month children were stunted. About 66% of babies received solids by sixth to eighth months; 91% were still breastfeeding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
180
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(218 citation statements)
references
References 33 publications
28
180
2
8
Order By: Relevance
“…Adequate feeding frequency of infants aged 6–11 months was 62%, whereas dietary diversity (a minimum of four or more food groups) for infants aged 6–11 months was only 24% (Marriott et al . 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Adequate feeding frequency of infants aged 6–11 months was 62%, whereas dietary diversity (a minimum of four or more food groups) for infants aged 6–11 months was only 24% (Marriott et al . 2011). …”
Section: Introductionmentioning
confidence: 99%
“…They found that reduced dietary diversity was a strong predictor of stunting. The WHO IYCF indicators have more recently been studied in DHS data from fourteen lowincome countries (12) . The data from all fourteen countries were pooled and analyses were performed for disaggregated age groups for each of the indicators.…”
mentioning
confidence: 99%
“…[3] Although significant gains has been registered in some IYCF practices (National Family Health Survey 3 and 14 country data), yet a large room for improvement exists. [5,6] The present study reported both core and optional indicators. Early IBF was practiced by more than half (57.6%) of the mothers studied.…”
Section: Discussionmentioning
confidence: 99%
“…[18,24,25] Similar situation prevailing in other countries of sub-continent including Nepal, Sri Lanka, and Bangladesh points to common underlying factors. [6,25,26] The situation with regard to consumption of iron-rich or iron-fortified foods is poor as well. [27,28] The situation therefore, is amenable to mitigation only if sustained and multilevel efforts are made.…”
Section: Discussionmentioning
confidence: 99%